Border enforcement and selection of Mexican immigrants in the United States - Fernando Antonio Lozano; Mary J. Lopez (Institute for the Study of Labor (IZA), 2010)
Since 1986 the United States has made considerable efforts to curb illegal immigration. This has resulted in an increase in migration costs for undocumented immigrants. More stringent border enforcement either deters potential illegal immigrants from coming to the U.S., or moves the point of crossing for illegal immigrants from traditional crossing routes to more inhospitable routes. These changes are likely to place a heavier burden on illegal immigrant women as they are more likely to be kidnapped, smuggled, or raped when crossing illegally. If migration costs are not the same for all migrants, higher migrating costs may result in a change in the number and in the composition of immigrants to the United States. In the face of higher migration costs, only immigrants with relatively high expected benefits of migration will choose to migrate. Based on our theoretical model, we test for three empirical results that are associated with a stronger selection of immigrant women from Mexico relative to men as a result of higher migration costs: 1) A decrease in the relative flow of older and highly educated undocumented immigrant women relative to men; 2) A change in the skill composition of immigrant women to men; and 3) An increase in the average earnings of those groups most affected by increased migration costs. Using data from the 1990, 2000 Decennial Census, and from the 2006-2008 American Community Survey we empirically confirm these predictions.
Keywords: J1; J2; J3; J6; 330; Immigration; gender; selection; border enforcement; Einwanderung; Mexikaner; Geschlecht; Frauen; Qualifikation; Grenze; Illegale Einwanderung; Migrationstheorie; Kosten; Migrationspolitik; USA